Taurine-mediated metabolic immune crosstalk indicates and promotes immunosuppression with anti-PD-1 resistance in bladder cancer - Liang, Zhengfang; Nong, Fengwei; Li, Zhenjie; Chen, Runmin; Zhao, Haoxu; Huang, Yongping (Frontiers in Immunology, 2025)
BackgroundBladder cancer (BLCA) remains heavily dependent on bacillus Calmette-Guérin (BCG) therapy due to the profound heterogeneity of its tumor microenvironment (TME) and deregulated metabolic landscapes. Taurine metabolism (TM) is a pivotal axis in BLCA, exhibiting dual roles in tumor progression and immune evasion. Deciphering the molecular mechanisms by which TM reprogramming fosters immunosuppression is imperative for advancing BLCA immunotherapy.MethodsThis study employed an integrative approach combining single-cell RNA sequencing (scRNA-seq), spatial transcriptomics (ST), and bulk transcriptome analyses to unravel taurine metabolic dysregulation in the BLCA TME. Computational frameworks such as Seurat and Monocle 3 were used to characterize cellular subpopulations, reconstruct differentiation trajectories, and model intercellular signaling networks. A taurine metabolic dysregulation index (TMs) was developed using TCGA cohorts, with survival modeling and machine learning methodologies deployed to assess its prognostic utility. Immuno-infiltration patterns and immunotherapeutic responsiveness were quantified via algorithms including ESTIMATE and TIDE. Mechanistic validation was achieved through co-culture systems.ResultsScRNA-seq profiling revealed significant perturbations in TM scores across epithelial cells, fibroblasts, and macrophages within the BLCA TME. High TMs clusters were enriched for Notch signaling and EGFR tyrosine kinase inhibitor resistance pathways. Spatial transcriptomics analyses highlighted spatiotemporal heterogeneity in taurine metabolic gene expression. The TMs index emerged as an independent prognostic biomarker, with high TMs patients demonstrating significantly shorter overall survival and synergistic prognostic deterioration in the context of high tumor mutational burden (TMB). High TMs tumors exhibited enrichment of immunosuppressive cell compartments and elevated immune checkpoint molecule expression. Mechanistically, FAAH knockdown in cancer-associated fibroblasts (CAFs) attenuated co-cultured BLCA cell viability, potentially mediated by CCL15 secretion.ConclusionThis study establishes that taurine metabolic dysregulation reconfigures intercellular signaling within the BLCA TME, driving immunosuppression and tumor progression. The TMs framework enables robust patient stratification and provides a mechanistic rationale for therapeutic strategies targeting TM in conjunction with immune checkpoint inhibitors, thus paving the way for advanced precision medicine approaches in BLCA.